Moisture Dependent Physical Properties of Chickling Pea - Nevase, Samodini S.; Nimkar, P. M.; Kadu, B. D. (Journal of Agricultural Engineering, 2014)
Effect of increase in moisture content from 6.12 to 31.42 % (d.b.) on physical properties of chickling pea of two varieties (lakh and lakholi) were evaluated by using standard procedures. Grain size, sphericity and grain volume increased due to change in the moisture content. The bulk density and true density decreased from 831 to 785 kg.mm-3 and 1333 to 1231 kg.mm-3, respectively, for lakh and 861 to 749 kg.mm-3 and 1303 to 1202 kg.mm-3,respectively, for lakholi. Thousand grain mass and bulk porosity increased from 78.68 to 83.98 g and 37.64 to 42.85 %, respectively, for lakh and 66.06 to 76.02 g and 36.20 to 41.58 %, respectively for lakholi. The angle of repose and terminal velocity increased from 31.49 to 37.82Â° and 12 to 13.71 m.s-1, respectively, for lakh and 25.78 to 31.08Â° and 11 to 13 m.s-1, respectively for lakholi.